2011
DOI: 10.1200/jco.2010.32.1877
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Status and Clinical Outcomes in a Large Cohort of Patients With Triple-Negative Breast Cancer

Abstract: A B S T R A C T PurposeTo evaluate the clinical outcomes and relationship between tumor size, lymph node status, and prognosis in a large cohort of patients with confirmed triple receptor-negative breast cancer (TNBC). Patients and MethodsWe reviewed 1,711 patients with TNBC diagnosed between 1980 and 2009. Patients were categorized by tumor size and nodal status. Kaplan-Meier product limit method was used to calculate overall survival (OS) and relapse-free survival (RFS). A Sidak adjustment was used for multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
106
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 18 publications
12
106
2
1
Order By: Relevance
“…This is particularly encouraging because the median overall survival of stage IV TNBC is 13 months in multiple large datasets and the median overall survival in our study has not been reached. Similarly, the median overall survival for stage III TNBC is less than 40% at 4 years in most large datasets and in our cohort appears to be longer although a randomized trial is necessary to confirm this exploratory observation (40,48).…”
Section: Discussionmentioning
confidence: 79%
“…This is particularly encouraging because the median overall survival of stage IV TNBC is 13 months in multiple large datasets and the median overall survival in our study has not been reached. Similarly, the median overall survival for stage III TNBC is less than 40% at 4 years in most large datasets and in our cohort appears to be longer although a randomized trial is necessary to confirm this exploratory observation (40,48).…”
Section: Discussionmentioning
confidence: 79%
“…In the present study, the general disease progression rate is 12.1% (29/239, the local recurrence rate is 6.7% (16/239) and the distant metastasis rate is 8.8% (21/239). These findings suggest that distant metastasis may exhibit a certain organ tendency in TNBC (23)(24)(25) and that the specific target organ metastasis may be associated with specific gene expression (26)(27)(28). Dent et al observed that the frequency of distant metastasis was significantly increased among patients with TNBC compared with non-TNBC patients (33.9 and 22.4%, respectively), and the risk of distant metastasis was found to be increased in the TNBC group (relative risk = 2.6) (18).…”
Section: Overall Survivalmentioning
confidence: 79%
“…Management of TNBC is a challenge due to lack of targeted therapy, aggressive tumor behavior and relatively poor prognosis (29). Although it has been reported that TNBC was chemosensitive, the results remained unsatisfactory (30)(31)(32)(33). Maximal effort should be made to select the best possible drugs for effective maintenance treatment of TNBC.…”
Section: Discussionmentioning
confidence: 99%